2016
DOI: 10.20517/2394-4722.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 expression in patients with colorectal cancer: a pilot study

Abstract: Aim: Excision repair cross complementation group 1 (ERCC1) has a key role in enhanced DNA damage repair caused by oxaliplatin-based therapy and may lead to resistance of these platinum drugs in colorectal cancer (CRC) patients. Hence, the present preliminary study aimed to explore the role of ERCC1 C/T polymorphism at codon 118 as well as its immunoreactivity in patients with primary CRC. Methods: ERCC1 polymorphism was studied using PCR-RFLP and ERCC1 protein expression was examined by immunohistochemistry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The previous method was employed to synthesize compound 5 with the following stoichiometric amounts; 1-(3,4-dichlorophenyl)piperazine (0.23 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 5 as orange reddish semisolid (0.16 g) in 71% yield; R f 0.56 (0.5:9.5, MeOH/DCM); IR (cast film) ν max = 3271, 2918, 1736, 1563, 1227, 1180, 1080, 1031, 803, 721 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) δ 8.09 (s, 1H), 8.00 (s, 1H), 7.88 (d, J = 9.2 Hz, 1H), 7.40 (d, J = 9.3 Hz, 1H), 7.28 (d, J = 8.7 Hz, 1H), 7.24 (d, J = 9.0 Hz, 1H), 7.09 (s, 1H), 6.95 (d, J = 2.8 Hz, 1H), 6.87 (dd, J = 8.6, 2.7 Hz, 1H), 6.80 (d, J = 8.6 Hz, 1H), 6.73 (dd, J = 8.9, 2.8 Hz, 1H), 6.54 (d, J = 2.6 Hz, 1H), 3.74 (s, 3H), 3.63 (s, 2H), 3.27−3.15 (m, 4H), 2.72−2.62 (m, 4H), OH and NH protons were not observed; 13 2-((4-(Bis(4-fluorophenyl)methyl)piperazin-1-yl)methyl)-4-((6chloro-2-methoxyacridin-9-yl)amino)phenol (6). The previous method was employed to synthesize compound 6 with the following stoichiometric amounts: 1-bis(4-fluorophenyl)methylpiperazine (0.29 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 6 as orange reddish semisolid (0.19 g) in 65% yield; R f 0.56 (0.5:9.5, MeOH/DCM); IR (cast film) ν max = 3275, 2919, 1737, 1566, 1255, 1217, 1181, 1032, 828, 722 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) δ 8.07 (s, 1H), 7.98 (d, J = 9.0 Hz, 1H), 7.84 (d, J = 9.2 Hz, 1H), 7.34 (m, 6H), 7.18 (d, J = 8.0 Hz, 1H), 7.06 (d, J = 1.8 Hz, 1H), 6.97 (m, 5H), 6.83 (dd, J = 8.5, 2.6 Hz, 1H), 6 4-((6-Chloro-2-methoxyacridin-9-yl)amino)-2-((4-(4hydroxyphenyl)piperazin-1-yl)methyl)phenol (7). The previous method was employed to synthesize compound 7 with the following stoichiometric amounts; 1-(4-hydroxyphenyl)piperazine (0.30 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 7 as orange reddish semisolid (0.17 g) in 59% yield; R f 0.58 (1.…”
Section: ■ Methods and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous method was employed to synthesize compound 5 with the following stoichiometric amounts; 1-(3,4-dichlorophenyl)piperazine (0.23 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 5 as orange reddish semisolid (0.16 g) in 71% yield; R f 0.56 (0.5:9.5, MeOH/DCM); IR (cast film) ν max = 3271, 2918, 1736, 1563, 1227, 1180, 1080, 1031, 803, 721 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) δ 8.09 (s, 1H), 8.00 (s, 1H), 7.88 (d, J = 9.2 Hz, 1H), 7.40 (d, J = 9.3 Hz, 1H), 7.28 (d, J = 8.7 Hz, 1H), 7.24 (d, J = 9.0 Hz, 1H), 7.09 (s, 1H), 6.95 (d, J = 2.8 Hz, 1H), 6.87 (dd, J = 8.6, 2.7 Hz, 1H), 6.80 (d, J = 8.6 Hz, 1H), 6.73 (dd, J = 8.9, 2.8 Hz, 1H), 6.54 (d, J = 2.6 Hz, 1H), 3.74 (s, 3H), 3.63 (s, 2H), 3.27−3.15 (m, 4H), 2.72−2.62 (m, 4H), OH and NH protons were not observed; 13 2-((4-(Bis(4-fluorophenyl)methyl)piperazin-1-yl)methyl)-4-((6chloro-2-methoxyacridin-9-yl)amino)phenol (6). The previous method was employed to synthesize compound 6 with the following stoichiometric amounts: 1-bis(4-fluorophenyl)methylpiperazine (0.29 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 6 as orange reddish semisolid (0.19 g) in 65% yield; R f 0.56 (0.5:9.5, MeOH/DCM); IR (cast film) ν max = 3275, 2919, 1737, 1566, 1255, 1217, 1181, 1032, 828, 722 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) δ 8.07 (s, 1H), 7.98 (d, J = 9.0 Hz, 1H), 7.84 (d, J = 9.2 Hz, 1H), 7.34 (m, 6H), 7.18 (d, J = 8.0 Hz, 1H), 7.06 (d, J = 1.8 Hz, 1H), 6.97 (m, 5H), 6.83 (dd, J = 8.5, 2.6 Hz, 1H), 6 4-((6-Chloro-2-methoxyacridin-9-yl)amino)-2-((4-(4hydroxyphenyl)piperazin-1-yl)methyl)phenol (7). The previous method was employed to synthesize compound 7 with the following stoichiometric amounts; 1-(4-hydroxyphenyl)piperazine (0.30 g, 1.0 mmol), acetaminophen (0.15 g, 1.0 mmol), 37% formaldehyde (0.10 mL, 5 mmol), and 6,9-dichloroacridine (0.28 g, 1.0 mmol) to afford 7 as orange reddish semisolid (0.17 g) in 59% yield; R f 0.58 (1.…”
Section: ■ Methods and Experimental Proceduresmentioning
confidence: 99%
“…It plays a pivotal role in nucleotide excision repair (NER) of bulky adducts and helix-distorting DNA lesions such as UV-induced pyrimidine-(6,4)-pyrimidone photoproducts (6-4PPs) and CPDs. ERCC1–XPF is also involved in DNA interstrand cross-link (ICL) repair in cells treated with platinum-based and other chemotherapeutic agents such as cyclophosphamide and mitomycin C (MMC) . In a recent study, 72% of colorectal cancer patients showed positive ERCC1 protein expression, which may be a useful marker for colorectal cancer patients . There is also evidence that ERCC1–XPF participates in DNA double-strand break (DSB) repair. , It thus contributes significantly to the response of cancer cells to a range of DNA-damaging chemotherapeutic agents and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They crosslink DNA molecules, causing extensive DNA damage and triggering apoptosis in cancer cells. However, in many cancer cells, the NER pathway is overactive due to the overexpression of ERCC1, which can diminish the therapeutic effectiveness of cisplatin and even lead to drug resistance [165][166][167][168]. Therefore, the design of selective NER/ERCC1 inhibitors holds promise in the enhancement of the efficacy of platinum-based treatments.…”
Section: Ercc1 Inhibitorsmentioning
confidence: 99%
“…There is evidence that the relative level of ERCC1 mRNA is a good marker for NER activity in human cancer cells, but it is unclear whether expression of this gene is important for other pathways of DNA repair [19, 20]. It has been previously shown that a high basal levels of ERCC1 is associated with poorer survival in patients with mCRC treated with oxaliplatin [21], although, surprisingly, no difference in tumor response was found [22, 23]. Although platinum drugs predominantly result in bulky DNA-distorting adducts and elicit NER, they can also induce inter-strand crosslinks that are repaired by the Fanconi pathways during S phase.…”
Section: Introductionmentioning
confidence: 99%